Influence of vacuum annealing on the dispersion of thin double niobium-copper films deposited onto oxide materials - Gab, I. I.; Stetsyuk, T. V.; Shakhnin, D. B. (Physics and Chemistry of Solid State, 2020)
The kinetics of dispersion of thin niobium-copper films deposited onto leucosapphire, alumina and zirconia ceramics and annealed in vacuum at temperatures up to 1100 °C with different exposition times at each temperature (from 5 up to 20 min) was studied. The double films consisted of two layers: the first metallization layer was 150 nm niobium nanofilm deposited onto the oxide surface, and the second copper layer 1,5 mm thick deposited over the first one as a solder was used for joining of metallized oxide samples. It was found that these films remain rather dense during heating up to 1050 °C; and after annealing at 1100 °C they decompose into individual fragments covering about 80% the area of the ceramic substrates even after annealing during 20 min. The kinetic curves for the dispersion of these films were plotted.